FORMATION OF LISTENING AND SPEAKING SKILLS AMONG SCHOOLCHILDREN (American Journal of Technology and Applied Sciences, 2022)
Learning to speak necessarily involves the formation of skills to build up various types of invocations: message, persuasion, description, approval, etc., to use a variety of questions, the ability to convey the content of what you read. Teaching a foreign language can make a significant contribution to the development of educational and communicative skills, since in the process of mastering speech in English, these skills, of necessity, become the object of increased attention.